Key features of mpox and its new presentations: a review - Aleksandra Bętkowska; Magdalena Maciejewska; Paulina Adrian; Konrad Szymański; Joanna Czuwara; Małgorzata Olszewska; Lidia Rudnicka (Przegląd Dermatologiczny, 2023)
Mpox (formerly called monkeypox) is a zoonosis caused by the monkeypox virus (MPXV). MPXV is an orthopoxvirus genetically and antigenically similar to the variola virus responsible for smallpox. Mpox is endemic to Central and West Africa, but in 2022 it spread rapidly leading to many cases in non-endemic countries. Human-to-human contact is currently the main mode of transmission. Patients usually present with a prodromal syndrome of fever, myalgia, headache, lymphadenopathy, and fatigue. The characteristic centrifugal rash with mucocutaneous lesions develops 1–4 days later. Lesion evolution typically follows a sequence of changes (macules, papules, vesicles, pustules, and crusts). The disease is mostly mild and self-limiting. Distinct clinical presentations have been observed during the ongoing outbreak. Prodromal symptoms may be less pronounced or absent. Lesions are located predominantly in the anogenital and perioral areas. Patients may present with few lesions clustered in the genital region or a solitary lesion. Mpox diagnosis is usually confirmed through viral DNA detection with polymerase chain reaction (PCR). There is no specific treatment for mpox. Therapy remains supportive in most cases. Antiviral drugs include tecovirimat, cidofovir, and brincidofovir. Antibody-based therapies are another treatment option. Smallpox vaccines should be considered for high-risk patients (pre-exposure prophylaxis) and following high-risk exposures (post-exposure prophylaxis). Comprehensive differential diagnosis and screening for co-infections with other sexually transmitted pathogens are needed.